Needle Gauge Affecting Recovery and in Vitro Maturation Rates of She-Camel Oocytes - Jaber, Ali Habeeb (American Journal of Biomedicine and Pharmacy, 2025)
In this study, she-camel oocytes were obtained from the slaughterhouse in order to determine the impact of needle gauge size on recovery and in vitro maturation rate (IVM). 110 oocytes were collected by aspiration method using two gauges size of needle (18g and 22g). The recovery rate (RR) and the in vitro maturation (IVM) rate were studied. The results showed a superiority of 22g vs the 18g in recovery rate 65/85(76.47%) vs 45/89(51.5%), with a reverse result were noticed in the IVM rate 29/41(70.73%) vs 36/58(62.07%) for 18g and 22g respectively. In conclusion, the use of needle with 18g is the best to use for in vitro maturation (IVM) purposes in she-camel, while when choosing the grade A oocytes only, it is best to use 22g for oocytes recovery.